Hubungan Antara Perkembangan Moral dengan Perilaku Prososial Pada Remaja di Perguruan Ki Hajar Dewantara Kotapinang - Istiana Istiana; Nur Wahyuni R. Hasibuan (Mahesa Research Center, 2021)
The purpose of this study was to look at the relationship between moral development and prosocial behavior in adolescents. The dependent variable in this study was prosocial behavior and the independent variable Moral Development. The population in this study were all students of class X SMK Ki Hajar Dewanatara Kotapinang, amounting to 392 samples in this study as many as 70 students / I of Ki Hajar Dewantara college Kotapinang. The sampling technique used purposive sampling. Measuring instruments used are the Moral Development scale and Prosocial Behavior scale using a Likert scale. Data management in this study uses Pearson product moment correlation techniques. The results of the study showed a correlation of 0.825 with p <0.000, this means there is a significant positive correlation between moral development and prosocial behavior. This means that the better the moral development, the higher the prosocial behavior, on the contrary the worse the moral development is the prosocial behavior. The determinant coefficient of the correlation is R2 = 0.681, which means that moral development contributes effectively to prosocial behavior by 68%, while the remaining 31.9%. mood. The hypothetical mean in this study for the moral development variable was 65 and for the prosocial behavior variable was 65. The empirical mean for moral development was 86.86 and the prosocial behavior was 85.51.